Optimizing recovery: the impact of training load in elite volleyball players - Rebelo, A.; Pereira, J. R.; Vande Broek, G.; Coelho-e-Silva, M. J.; Elferink-Gemser, M. T.; Valente-dos-Santos, J. (International Journal of Sports Medicine, 2025)
This study aimed to analyze the relationships between training load metrics and various dimensions of recovery over the course of 105 days during the competitive season. This study included 14 elite male volleyball players who participated in 95 training sessions and 18 matches. The session rating of perceived exertion and inertial measurement units were utilized to measure internal and external training loads, respectively. Biological recovery was assessed using the countermovement jump test, while social and psychological recoveries were measured through the RESTQ-Sport. Relationships were examined using linear mixed-effect models to account for repeated measures across players and time points. The results revealed that chronic external training loads negatively influenced the biological recovery, with increases in chronic external training loads associated with a longer time to take-off (ß=- 0.008, p=0.03) and a reduced modified reactive strength index (ß=- 0.008, p=0.047). Social recovery was influenced by internal training load metrics, with acute internal training loads increasing social stress (ß=- 3.512, p=0.034). For psychological recovery, chronic internal training loads and the acute:chronic internal training load ratio were linked to higher emotional exhaustion (ß=- 0.013, p=0.029; ß=0.021, p<0.001, respectively). These findings highlight the critical role of external load management in the biological recovery and the relevance of subjective internal load measures in monitoring social and psychological recovery dimensions. Coaches are encouraged to integrate time-based neuromuscular metrics and perceptual load assessments into their recovery monitoring protocols to optimize athletes` well-being and performance.